Translating phototherapeutic indices from in vitro to in vivo photodynamic therapy with bacteriochlorins. Issue 5 (1st May 2018) - Luz, André F.S.; Pucelik, Barbara; Pereira, Mariette M.; Dąbrowski, Janusz M.; Arnaut, Luis G.
Abstract : Objective: To compare hydrophilic and lipophilic bacteriochlorin photosensitizers in the photodynamic therapy of cancer, and relate their properties and in vitro phototoxicities to the efficacy of in vivo PDT treatments. Materials and Methods: Photochemical characterization of a hydrophilic bacteriochlorin (F2 BOH) photosensitizer, and its use in PDT was compared with the performance of a closely related but water‐insoluble bacteriochlorin (F2 BMet or redaporfin). Biodistribution, pharmacokinetics, skin photosensitivity, PDT efficacy and immune responses of two bacteriochlorins were compared. PDT in vitro employed CT26 colon carcinoma cells. BALB/c mice bearing CT26 cells were treated according to a protocol where the illumination of the subcutaneous tumor is performed 15 minute after intravenous administration of the photosensitizer, while it is in the vascular compartment (vascular‐PDT). Results: F2 BOH has photochemical properties comparable to redaporfin and both are promising photosensitizers for PDT. Although, F2 BOH is 10 times less phototoxic in vitro than redaporfin, the phototoxicity of F2 BOH in vascular‐PDT is comparable to that of redaporfin. This is consistent with the fact that the vasculature is the main target of vascular‐PDT. F2 BOH‐PDT led to long‐term cures and stimulation of the immune system. Conclusion: F2 BOH is soluble in aqueous media, photostable, has a convenient elimination half‐life of 44 hours and leads to very low skin photosensitivity one week after administration. F2 BOH and redaporfin are both very phototoxic in vascular‐PDT, but this could not be anticipated from their widely different phototherapeutic indices in vitro . PDT with F2 BOH enabled long‐term cures of BALB/c mice with subcutaneously implanted CT26 tumors, and the cured mice rejected tumor re‐inoculation one year after the treatment. Lasers Surg. Med. 50:451–459, 2018. © 2018 Wiley Periodicals, Inc.